Emergency laparoscopic cholecystectomy for intraabdominal hemorrhage in a patient with a left ventricular assist device: a case report - Akihiko Takagi; Erina Nagai; Takeo Toda; Hayato Kosaka; Hisato Ishimatsu; Yusuke Kyoden; Takehide Akimoto; Hideyuki Kanemoto; Noriyuki Oba (Surgical Case Reports, 2019)
Abstract Background Continuous-flow left ventricular assist devices (LVADs), called “second generation LVADs,” have significantly improved the survival and quality of life outcomes. Accordingly, non-cardiac surgery in a patient with LVADs has required for conditions not directly related to their LVADs. And the management of bleeding in non-cardiac site remains one of long-term critical topics. Laparoscopic approach is useful in a patient with LVADs; however, there have been only few clinical reports. This report describes the first case of laparoscopic cholecystectomy (LC) for intraabdominal hemorrhage from the gallbladder serosa in a patient with LVADs. Case presentation A 56-year-old man with an LVAD had undergone LVAD (Jarvik 2000™; Jarvik Heart, Inc., New York, NY, USA) implantation at 53 years of age. He was in shock, and contrast-enhanced computed tomography revealed abdominal hemorrhage from the gallbladder serosa. Emergency laparoscopic cholecystectomy was performed. We could avoid injury of the LVADs driveline, which was located across the upper abdominal midline, near the right hypochondriac region, by laparoscopic approach. LVADs (Jarvik 2000) did not disturb the operating field because of its smaller size. There were no intra- and postoperative complications. Conclusions Laparoscopic approach is useful and safe in a patient with LVADs for abdominal surgery. We could perform LC for intraabdominal hemorrhage from gallbladder serosa safety.